Performance analysis of hybrid WiFi and TV white space links - Lamola, Mokwape Magdeline (Department of Computer Science, 2021)
Internet access has the potential to improve economic growth in developing countries, yet in developing countries with emerging economies, such as South Africa, Internet access opportunities are not evenly distributed. This digital divide exists between urban and rural areas and even within urban areas in many developing countries. Urban areas are densely populated - simplifying telecommunication infrastructure roll-out, whereas rural areas are sparsely populated - making the roll-out of telecommunication infrastructure considerably more complex and expensive. This digital divide poses a significant challenge since a large portion of the developing country's population is based in rural areas. Cellular, satellite and some pockets of WiFi technologies are mostly used to provide access in rural areas. Although these technologies help mitigate connectivity challenges in rural areas, they are often costly and provide limited broadband access. The high cost of access in rural areas is due to the lack of fibre for backhaul that provides cost effective bulk wholesale capacity and the use of costly satellite links or cellular links for Internet access. Cost-effective technology alternatives such as WiFi and/or Television White Space (TVWS) can provide an effective approach to provide affordable last mile and middle mile connectivity for Internet access in many of these poorly connected areas. TVWS provides excellent coverage and penetration through vegetation, buildings since it utilizes spectrum in the UHF bands currently used for Television broadcasting to offer broadband wireless connectivity. Although TVWS has good propagation characteristics in some non-line-ofsight (NLOS) scenarios and can offer better coverage than WiFi, thanks to the mass production and massive industry and development support behind it, WiFi provides low-cost connectivity with better throughput speeds in line-of-sight (LOS) scenarios. Previous research has focused on the characteristics and performance of TVWS and WiFi in isolation. This study aims to describe how their individual characteristics can then be used to compliment each other for improvement in the last-mile access. This work looked at the performance of WiFi and TVWS technology in different settings, including line-of-sight, non-line-of-sight environments and using different combinations of these technologies. Experiments focused on the performance of WiFi (IEEE 802.11a) and TVWS (IEEE 802.11g cards downconverted to UHF) with an objective to help improve connectivity in areas with poor coverage, due to environmental factors, such as vegetation and distance. The study utilized the Council of Scientific and Industrial Research's (CSIR's) Meraka Institute custom built White Space Mesh Node (WSMN) equipped with WiFi and TVWS radio interface cards to carry out the experiments. The study particularly focuses on the 5 GHz Wi-Fi and Ultra High Frequency (UHF) 530 to 600 MHz frequency bands. The study presents an analysis of data collected over the dual-radio wireless network in indoor and outdoor environments. Presentation of this data follows measurements of single radio and aggregate radio link traffic collected in various line-of-sight and non-line-of-sight environments. These measurements deduce the effects of environment on 5 GHz and TVWS frequency band, effects of modifying performance parameters, improvement or degradation of aggregated TVWS WiFi links, and the usage of the measured performance data for network planning. Each experiment tests different combinations of radio settings, such as channel, transmit power and channel width to measure throughput, signal strength, packet loss, and Signal to Noise Ratio. These tests were done in both indoor and outdoor environments. The results collected and presented in this work show that although TVWS has superior propagation characteristics compared to WiFi, its performance is often poorer than WiFi when there is clear line-of-site and at shorter distances. The study, in addition, presents data that shows that the overall radio performance in a network is affected by more than just spectrum availability in space or time, but also by radio settings and the environment. The study also goes on to show that aggregated links, that combine both TVWS and WiFi, do not always lead to better network performance. The study lastly presents tailored scenarios of single and aggregated radio links that lead to better performance with the hope that these will help network designers and researchers make better-informed decisions on how to use available radio resources effectively.